Vitamin D metabolites across the menstrual cycle: a systematic review - Anita Subramanian; Alison D. Gernand (BMC, 2019)
Abstract Background Accurate estimation of vitamin D status is important for health research and can impact prevention and treatment of deficiency in women of reproductive age. We aimed to assess if blood concentrations of 25-hydroxyvitamin D [25(OH)D] or 1,25-dihydroxyvitamin D [1,25(OH)2D] change across the menstrual cycle. Methods We conducted a systematic search in PubMed, Web of Science, CAB and BIOSIS of literature published until December 2018 which reported concentrations of vitamin D metabolites at two or more identified points among women with regular menstrual cycles. Results Ten longitudinal studies met the inclusion criteria; nine studies measured 1,25(OH)2D and five studies measured 25(OH)D. Study size ranged from 5 to 47 subjects, with an age range of 18-47 years. One study found a decrease in concentration of 25(OH)D in the periovulatory and luteal phase. Four studies found no changes in concentrations of 25(OH)D. Two studies found a rise in 1,25(OH)2D within the follicular phase, including a 128% increase from day 1 to 15 and a 56% increase from day 0 to 12. Two studies found rises in 1,25(OH)2D concentrations from the follicular to luteal phase of 13 and 26%. Five studies did not find any changes in concentrations of 1,25(OH)2D. Conclusions No conclusion can be drawn on the pattern of 1,25(OH)2D concentrations across the normal menstrual cycle due to inconsistencies in study findings. Evidence is currently insufficient to assess 25(OH)D concentrations across the cycle. Future studies should aim to measure 1,25(OH)2D and 25(OH)D longitudinally, to understand relationships with other hormones and the potential impact on estimates of vitamin D deficiency.